2016
DOI: 10.1515/amm-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Microstructure and Corrosion Resistance of Sand Cast Aluminum Alloys

Abstract: The influence of different types of precipitation on the corrosion behavior was investigated in three aluminum-siliconmagnesium alloys. The microstructures of the alloys were studied through optical (OM) and scanning electron microscopy (SEM). The structures consisted of an α-Al solid solution matrix, Si eutectic crystals, secondary phases AlFeSi and AlMgFeSi (Chinese script), as well as Mg2Si. The corrosion behavior was examined with the use of a potentiodynamic polarization test followed by a SEM surface ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…However, they may behave differently depending on the material investigated. Based on the literature data for aluminum and its alloys for example, [2][3][4][5][6] it can be concluded that two microstructural features have the most significant impact on corrosion behavior: grain size and second-phase/ intermetallic particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, they may behave differently depending on the material investigated. Based on the literature data for aluminum and its alloys for example, [2][3][4][5][6] it can be concluded that two microstructural features have the most significant impact on corrosion behavior: grain size and second-phase/ intermetallic particles.…”
Section: Introductionmentioning
confidence: 99%
“…Dobkowska et al [4] reported the influence of the formation of intermetallic compounds of AlFeSi, AlMnFeSi, and AlMgFeSi on the corrosion resistance of AlSi5, AlSi7Mg, and AlSi10Mg. The measured corrosion densities were significantly lower than those obtained by other authors using similar alloys (Table S2).…”
Section: Corrosion Resistance Of Cast Aluminum Alloys Obtained By Gramentioning
confidence: 99%
“…SEM micrographs and EDS analysis performed in (a) AlSi7Mg and (b) AlSi10Mg, respectively. Reprinted with permission of[4].…”
mentioning
confidence: 99%
“…Therefore, mechanical properties of Al-Si alloys have also been extensively investigated. By contrast, the corrosion resistance of Al-Si alloys is not sufficiently researched [18][19][20][21][22][23][24][25]. Silicon, as a major alloying element in aluminium alloys, is primarily responsible for good castability, low density (2.34 g cm -3 ), and reduction of thermal expansion coefficient.…”
Section: Introductionmentioning
confidence: 99%